Efficacy of a tool to predict short-term mortality in older people presenting at emergency departments: Protocol for a multi-centre cohort study. (May 2018) - Cardona, Magnolia; Lewis, Ebony T.; Turner, Robin M.; Alkhouri, Hatem; Asha, Stephen; Mackenzie, John; Perkins, Margaret; Suri, Sam; Holdgate, Anna; Winoto, Luis; Chang, Chan-Wei; Gallego-Luxan, Blanca; et al.
Highlights: The CriSTAL checklist is an objective and practical tool to predict short-term death. Validation in emergency department aims to reduce clinicians' prognostic uncertainty. The ultimate goal is to encourage timely end-of-life conversations. Abstract: Background: Prognostic uncertainty inhibits clinicians from initiating timely end-of-life discussions and advance care planning. This study evaluates the efficacy of the CriSTAL (Cri teria forS creening andT riaging toA ppropriate aL ternative care) checklist in emergency departments. Methods: Prospective cohort study of patients aged ≥65 years with any diagnosis admitted via emergency departments in ten hospitals in Australia, Denmark and Ireland. Electronic and paper clinical records will be used to extract risk factors such as nursing home residency, physiological deterioration warranting a rapid response call, personal history of active chronic disease, history of hospitalisations or intensive care unit admission in the past year, evidence of proteinuria or ECG abnormalities, and evidence of frailty to be concurrently measured with Fried Score and Clinical Frailty Scale. Patients or their informal caregivers will be contacted by telephone around three months after initial assessment to ascertain survival, self-reported health, post-discharge frailty and health service utilisation since discharge. Logistic regression and bootstrapping techniques and AUROC curves will be used to test the predictive accuracy of CriSTAL for death within 90 days of admission and in-hospital death. Discussion: The CriSTAL checklist is an objective and practical tool for use in emergency departments among older patients to determine individual probability of death in the short-term. Its validation in this cohort is expected to reduce clinicians' prognostic uncertainty on the time to patients' death and encourage timely end-of-life conversations to support clinical decisions with older frail patients and their families about their imminent or future care choices.